A new species of Telenomus Haliday (Hymenoptera: Platygastridae) egg parasitoid of Parides ascanius (Cramer) (Lepidoptera: Papilionidae), a threatened species from Brazil - Almeida, Gilberto De Souza Soares De; Loiácono, Marta Susana; Margaría, Cecilia Beatriz; Monteiro, Ricardo Ferreira (Zootaxa, 2015)
Telenomus parides Loiácono et Margaría sp. nov., is described and illustrated based on specimens reared from the eggs of Parides ascanius (Cramer). Parides ascanius is a threatened papilionid, which is endemic to the restingas of the Atlantic Forest of Rio de Janeiro, Brazil. The new Telenomus species is gregarious endoparasitoid and belongs to the Telenomus californicus species complex.